Heterogeneous consumers, segmented asset markets, and the effects of monetary policy - Enders, Zeno (Bonn Econ Discussion Papers, 2010)
This paper examines the implications of segmented assets markets for the real and nominal effects of monetary policy. I develop a model, in which varieties of consumption bundles are purchased sequentially. Newly injected money thus disseminates slowly through the economy via second-round effects and induces a non-degenerate, long-lasting heterogeneity in wealth. As a result, the effective elasticity of substitution differs across households, affecting optimal markups chosen by producers. In line with empirical evidence, the model predicts a short-term inflation-output trade-off, a liquidity effect, countercyclical markups, and procyclical profits and wages after monetary shocks. -- Segmented Asset Markets ; Monetary Policy ; Countercyclical Markups ; Liquidity Effect ; Limited Participation
Keywords: Arbeitspapier; Graue Literatur